2005
DOI: 10.1186/1472-6874-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Race and satisfaction in general OB/GYN clinics

Abstract: Background: The purpose of this study was to test the hypothesis that racial differences in satisfaction can be found among OB/GYN patients on a US naval base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The satisfaction was higher than a study was reported 56.1% of the users of the general OB/GYN clinics were satisfied with service another study from Malaysia reported that the mean of the total satisfaction score was 59.2, this satisfaction score was also lower than satisfaction of current study. 12,13 More than half of the respondents were satisfied with appointments system but around 34 % of the respondents were not satisfied with it. The respondents who were not satisfied with appointment system may due to their education back ground or they may not similar to the appointment system and also it could be due to patient's age, elderly may have difficulty to make appointment.…”
Section: Discussionmentioning
confidence: 99%
“…The satisfaction was higher than a study was reported 56.1% of the users of the general OB/GYN clinics were satisfied with service another study from Malaysia reported that the mean of the total satisfaction score was 59.2, this satisfaction score was also lower than satisfaction of current study. 12,13 More than half of the respondents were satisfied with appointments system but around 34 % of the respondents were not satisfied with it. The respondents who were not satisfied with appointment system may due to their education back ground or they may not similar to the appointment system and also it could be due to patient's age, elderly may have difficulty to make appointment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may prefer to receive their care at a satellite clinic. 10 The reasons studied have included parking, less congestion, and more personal style of service. Strategic placement of facility locations in areas of easy access, parking, and away from urban congestion are significant factors in patient satisfaction-assuming the medical care is perceived as equivalent across sites.…”
mentioning
confidence: 99%